A Scoping Review of Otologic Manifestations of Hematologic Malignancies - Raymond, Mallory J; Ottinger, Allie; Rowley, M Andrew; Bobian, Michael; Dornhoffer, Jim; Brennan, Emily; Rizk, Habib G (Otology & neurotology, 2024)
To examine the otologic and neurotologic symptoms, physical examination findings, and imaging features secondary to hematologic malignancies. Following Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines, databases, including PubMed, Scopus, and CINAHL, were searched for articles including patients with otologic manifestations of leukemia, lymphoma and multiple myeloma. Data collected included patient and study demographics, specific hematologic malignancy, timing and classification of otologic symptoms, physical examination findings, imaging features and methods of diagnosis. Pooled descriptive analysis was performed. Two hundred seventy-two articles, of which 255 (93.8%) were case reports and 17 (6.2%) were case series, reporting on 553 patients were identified. Otologic manifestations were reported on 307 patients with leukemia, 204 patients with lymphoma and 42 patients with multiple myeloma. Hearing loss and unilateral facial palsy were the most common presenting symptoms for 111 reported subjects with leukemia (n = 46, 41.4%; n = 43, 38.7%) and 90 with lymphoma (n = 38, 42.2%; n = 39, 43.3%). Hearing loss and otalgia were the most common presenting symptoms for 21 subjects with multiple myeloma (n = 10, 47.6%; n = 6, 28.6%). Hearing loss and unilateral facial palsy were the most common otologic symptoms indicative of relapse in subjects with leukemia (n = 14, 43.8%) and lymphoma (n = 5, 50%). Hearing loss, facial palsy, and otalgia might be the first indication of a new diagnosis or relapse of leukemia, lymphoma, or multiple myeloma. Clinicians should have a heightened level of suspicion of malignant etiologies of otologic symptoms in patients with current or medical histories of these malignancies.